Historical Institutional Differences and Entrepreneurship: Socialist Legacy in Vietnam - Fisch, Christian; Wyrwich, Michael; Lanh Nguyen, Thi; Block, Jörn H. (Senate Hall, 2021)
We study the case of Vietnam to assess the long-lasting role of institutional and historical legacy on entrepreneurial outcomes. In particular, we investigate the detrimental effect of socialist insti-tutions on entrepreneurship. Vietnam offers a unique quasi-experimental setting because the country was divided into the socialist North and the nonsocialist South for a relatively short period of two decades. After reunification, the South adopted the institutional framework conditions of the North. To assess the relationship between socialist history and entrepreneurship in this unique setting, we survey more than 3,000 North and South Vietnamese individuals more than four decades after the reunification of the country. We find that North Vietnamese respondents have lower entrepreneurship intentions, are less likely to select into entrepreneurship education programs, and are less willing to engage in a business takeover. These patterns indicate the persistence of historical differences in institutional framework conditions on entrepreneurship. We conclude by outlining the implications of a socialist legacy for entrepreneurship theory and policymakers.
Keywords: socialism|Vietnam|institutions|entrepreneurship intention|entrepreneurship education|takeover vs. new venture startup